2021
DOI: 10.31246/mjn-2021-0045
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with undernutrition among Dayak children in rural areas of Sarawak, Malaysia

Abstract: Background: Undernutrition among children has become a major public health issue due to the high risk of morbidity and mortality involving this vulnerable age group. This study focused on the rural population, especially among the Dayak children in Sarawak, Malaysia. Methodology: This community-based cross-sectional study was conducted in Sarawak’s rural areas using a multistage stratified cluster sampling technique. Data were collected through face-to-face interviews using an interviewer-guided questionnaire.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
0
3
Order By: Relevance
“…This finding is consistent with NHMS (2019), where the prevalence of undernutrition (underweight 14.1%; stunting 21.8%; wasting 9.7%) was higher than overnutrition (overweight 5.6%; obese 5.6%) (IPH, 2020). In Sarawak, a study conducted by Rahman, Kiyu & Seling (2021) reported that the proportion of wasting was lower than in the present study, which was 6.9%. The difference in proportion may be due to different demographic characteristics, as the previous study was conducted among the Dayak community and in all divisions of Sarawak.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…This finding is consistent with NHMS (2019), where the prevalence of undernutrition (underweight 14.1%; stunting 21.8%; wasting 9.7%) was higher than overnutrition (overweight 5.6%; obese 5.6%) (IPH, 2020). In Sarawak, a study conducted by Rahman, Kiyu & Seling (2021) reported that the proportion of wasting was lower than in the present study, which was 6.9%. The difference in proportion may be due to different demographic characteristics, as the previous study was conducted among the Dayak community and in all divisions of Sarawak.…”
Section: Discussioncontrasting
confidence: 85%
“…Besides that, it might be due to the difference in the proportion of poor households between these two studies. Poor household is one of the factors related to wasting in children (Rahman et al, 2021). Undoubtedly, the proportion of poor households in this study (74.2%) was much higher than the study conducted by Rahman et al (2021), which was 27.3%.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation